On the way to bridging the gap between the mental apparatus and the neurobiological layer. Issue 2 (3rd July 2017) - Dietrich, Dietmar; Zucker, Gerhard; Doblhammer, Klaus
Abstract : The mental apparatus – mind, psyche, soul – expresses itself in thought, play, love, creating, sex, planning, in fact in all human activities. Its foundation is the nervous system, as it is the central information system of the human being. For those interested in the connection between the neuronal level and the mental level, how is it possible to comprehend and model the connection between the neurobiological and the psychological? What does a natural scientific model of the mental apparatus look like? These questions led to the SiMA project (Simulation of the Mental Apparatus & Application). This article surveys the foundations of information theory and computer technology that underlie the SiMA project, and explains how the view of the neuropsychoanalytic world can be mapped into a model that can then be simulated and tested. The first results of several simulated case studies are described, suggesting that SiMA provides a way to validate theories of neuropsychoanalysis.